THE INFLUENCE OF VOICE OF AMERICA (VOA) LEARNING ENGLISH IN READING COMPREHENSION AT SMAN 18 MAKASSAR - Clara, Jepita; Hamid, Restu Januarty; Sahib, Nurfaizah (THE ACADEMIC: ENGLISH LANGUAGE LEARNING JOURNAL, 2023)
The objective of this research aimed to find out the influence of using Voice of America (VOA) Learning English on students’ reading comprehension of the eleventh grade students at SMAN 18 Makassar. The design of this research was an experimental research. The population of this research were the eleventh grade students of SMAN 18 Makassar. The sample of this research was the students in XI science 1. The research instruments used by the researcher were test and questionnaires. The test was used to measure the students’ reading comprehension before and after treatment and the questionnaire was used to collect information about the students’ interest in learning reading by using VOA Learning English. The form of the test was multiple choices and consist of twenty items. The techniques used in collecting the data were pre-test and post-test. Pre-test was administered before the researcher began the teaching learning process and post-test was administered after treatment. In testing the hypothesis, t-test was employed. The calculation was done by using SPSS v.20 The findings of this research was T-test result revealed that sig. (tailed) was 0.000. The outcome indicated that the sig. (2-tailed) table was less significant than the level of significance. As a result, the alternative hypothesis (H1) was accepted, while the null hypothesis (H0) was rejected. It means that implementing Voice of America (VOA) Learning English in the eleventh grade of Science 1 at SMAN 18 Makassar in the academic year 2023/2024 can improve students' reading comprehension ability. Therefore, it can be concluded that teaching English reading comprehension by using VOA Learning English had a significant influence and it was more effective.